Polymorphic transitions of V-type amylose upon hydration and dehydration - Guo, Jiayue; Ziegler, Gregory R.; Kong, Lingyan (Food hydrocolloids, 2022)
In the current study, V6, V7 and V8 amyloses were prepared, their crystalline polymorphic transitions upon hydration at different moisture conditions examined by wide-angle X-ray diffraction (XRD), and the relative degrees of crystallinity calculated. Upon the formation of V7 or V8 crystals, the XRD peaks shifted to lower Bragg angles as compared to V6h due to the expansion of the amylose helices. Conditioning at 75% equilibrium relative humidity (ERH) transformed V6a and V7 amyloses to the V6h pattern. Long-term vapor hydration at 100% ERH or total hydration by immersion in water transformed all V-type XRD patterns to the B-type with decreased degrees of crystallinity. Upon dehydration by ethanol wash, the relative crystallinities of all V-type amyloses were increased, while the crystalline patterns remained mostly unchanged. Such explicit study of polymorphic transitions revealed by XRD can help establish optimal conditions for the encapsulation of bioactive compounds with V-type amyloses and provide insights for novel food product developments. [Display omitted] •Four types of V amylose (V6a, V6h, V7, and V8) subject to hydration and dehydration•Hydration at 75% equilibrium relative humidity (ERH) transformed V6a and V7 to V6h•Total and long-term vapor hydration at 100% ERH transformed all V types to B type•Dehydration increased relative crystallinities of all V-type amyloses